The Protective role of Pomegranate seed oil (Pometon) on kidney (functional and structural) damage induced by Methionine overload in adult female Rabbits - Salman, Ahmed Dawood (The Iraqi Journal of Veterinary Medicine, 2014)
This study was designed to investigate the protective effect of Pomegranate seed oil (PSO) on kidney damage induced by methionine overload in adult female rabbits. Twenty four adult female local rabbits were randomly divided into four equal groups, and they were treated daily for 42 days,as fallow: the first group (C): rabbits were received ordinary corn oil orally, serving as control, while aniamls in the second group T1 were intubated with methionine (100 mg/kg BW) orally and animals in third group (T2) were intubated with methionine (100mg/kg BW) plus pometon (30mg/kg BW) diluted in corn oil wihle, rabbits in fourth group (T3) were intubated with pometone (30 mg/kg BW) diluted in corn oil.Fasting blood samples were collected from all experimental groups at 0, 21, and 42 days of experiment to study the parameters: Serum creatinine (SC) concentration and Blood urea nitrogen (BUN) concentration. Sections of kidney were assessed for histopathological studies. The result revealed that exposure of animals to methionine in group (T1) for 42 days caused a significant increase (P<0.05) in SC, BUN, concentrations as comparing to pomegranate treated groups and control. While oral intubation of PSO caused significant decrease (P<0.05) in the previous and correct the values near that of the control. Exposure to methionine overload showed severe acute cellular degeneration with mononuclear cells infiltration between renal tubules while there was no clear pathlogical lesions in kidney section after PSO intubation. In conclusion, it seems that Pomegranate seed oil intubation possessed renoprotactive (functional and structural) effect against deleterious damage induced by Methionine overload in rabbits.